High ionic conductivity of Lu2O3–TiO2 co-doped Bi2O3 ceramics. (5th February 2021) - Luo, Zeyang; Wang, Huan; Ma, Yuxin; Zhang, Guodong; Yan, Duanting; Bai, Xinyu; Wang, Dejun; Liu, Runru
Abstract: In this study, a promising electrolyte material Bi0.76 Lu0.16 Ti0.08 O1.5+ δ (abbreviated as '8T16LSB') with high oxygen ion conductivity was obtained by co-doping with Lu2 O3 and TiO2 into Bi2 O3 . The phase composition, microstructure, and conductivity of TLSB ceramics were respectively investigated by x-ray diffraction, scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS). XRD results exhibited that the sintered TLSB ceramics with an unchanged total doping concentration of 24 mol.% existed as a cubic fluorite structure. SEM results showed that the TLSB pellets were relatively dense. The relationship between temperature and conductivity showed that the 8T16LSB ceramic exhibited the highest conductivity of 0.56 S cm −1 at 700 °C, which was higher than the value of 0.37 S cm −1 for the representative single-doping Er0.4 Bi1.6 O3 (abbreviated as '20ESB'). The results certified that the electrochemical performance of Bi2 O3 was promoted by the co-dopant of Lu 3+ and Ti 4+ .